Trimethoprim-Sulfamethoxazole-Induced Aseptic Meningitis: A Rare Presentation of Commonly Used Antibiotic - Salem Agabawi (Case Reports in Infectious Diseases)
Drug-induced aseptic meningitis is a rare medical condition with trimethoprim-sulfamethoxazole being one of the most common antimicrobial agents associated with it. Here, I report a case of a 56-year-old male who presented to a health care facility with shock and meningitis-like syndrome in two occasions, one year apart following an exposure to trimethoprim-sulfamethoxazole for treatment of skin/soft tissue infection. Investigations did not reveal an infectious etiology in the two presentations. The patient improved with supportive care and withdrawal of the offending agent. In the two admissions, the patient improved following stopping the offending drug in addition to supportive care. The diagnosis of trimethoprim-sulfamethoxazole-induced aseptic meningitis was the most likely explanation for this case. Trimethoprim-sulfamethoxazole-induced aseptic meningitis is rare although it is a life-threatening side effect of TMP/SMX; therefore, the clinicians should keep the diagnosis of drug-induced aseptic meningitis in the differential diagnosis of aseptic meningitis in the appropriate clinical setting as early withdrawal of the culprit drug and supportive measurements will lead to early recovery.